(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article is based on research that had as its source the virtual pages of theater groups In the city of Medellín, city halls, press, festivals and academic magazines. After presenting the concepts involved and the methodology, common aspects are sought and then the specificities of each set are observed, having as main source their self-defining texts. What can a remote search do in the search for clues in a group theater?